2014
DOI: 10.1007/s10856-014-5286-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant types on the biocompatibility of electrospun HAp/PHBV composite nanofibers

Abstract: Bone tissue engineering literature conveys investigations regarding biodegradable polymers where bioactive inorganic materials are added either before or after electrospinning process. The goal is to mimic the composition of bone and enhance the biocompatibility of the materials. Yet, most polymeric materials are hydrophobic in nature; therefore, their surfaces are not favorable for human cellular adhesion. In this sense, modifications of the hydrophobic surface of electrospun polymer fibers with hydrophilic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…Benzyl triethylammonium chloride (BTEAC) is a one example of QACs [44]. Some researchers have incorporated BTEAC into polymer solution in order to change the electrical conductivity and surface tension of the solution and to increase spinnability during the electrospinning of nanofibers [45][46][47][48][49]. For instance, You et al [50] added BTEAC to a solution of poly(lactic-co-glycolic acid) (PLGA) during electrospinning to obtain various diameters of BTEAC-PLGA nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Benzyl triethylammonium chloride (BTEAC) is a one example of QACs [44]. Some researchers have incorporated BTEAC into polymer solution in order to change the electrical conductivity and surface tension of the solution and to increase spinnability during the electrospinning of nanofibers [45][46][47][48][49]. For instance, You et al [50] added BTEAC to a solution of poly(lactic-co-glycolic acid) (PLGA) during electrospinning to obtain various diameters of BTEAC-PLGA nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, addition of HA NPs into NFs modifies hydrophobicity of electrospun NFs that adhere to more favorable human cells. For this matter, Suslu et al studied electrospun HAp/PHBV mats, and they found that surfactants strongly activate the precipitation rate of the apatite-like particles and decrease the percentage crystallinity of the HAp/PHBV mats [89]. Li et al studied the dispersion of HA in PCL NFs and found that the tensile strength and Young’s modulus increased.…”
Section: Applications Of Ceramic Electrospun Matsmentioning
confidence: 99%
“…When the weight and volume percentages of nanoparticles in polymers increase, it becomes even more difficult to achieve uniform dispersion. A surface modifier (for example, surfactant) is often utilized to improve dispersion of nanoparticles by acting as a mediator between the nanoparticles and polymers during mixing . However, surfactants often raise concerns on toxicity and other associated complications for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…A surface modifier (for example, surfactant) is often utilized to improve dispersion of nanoparticles by acting as a mediator between the nanoparticles and polymers during mixing. 5,6 However, surfactants often raise concerns on toxicity and other associated complications for medical applications. Therefore, the objective of this research is to investigate the use of mechanical mixing methods, particularly high-power sonication and dual asymmetric centrifugal (DAC) mixing, to improve dispersion of nanoparticles in polymer-based nanocomposites while circumventing surfactants.…”
Section: Introductionmentioning
confidence: 99%